The Influence of Workload, Work Facilities, and Supervision on the Performance of Outbound Unit Employees at PT JNE Medan Main Branch - Dinda Aulia; Darmilisani Darmilisani; Daud Arifin (Journal of Management, Economic, and Accounting, 2026)
The main objective of this research is to find out how PT JNE Cabang Utama Medan's leadership, working conditions, and physical plant affect the company's productivity. Analytical and quantitative approaches were utilized in this study. For the purpose of data collection, the study asked 55 randomly selected individuals to fill out surveys. To create primers, we turned to SPSS version 24's data extraction methodologies. We used multiple linear regression to look for correlations in the data between the dependent and independent variables. According to the results, workers are significantly more efficient when they have good leadership, a nice place to work, and enough tools. The regression analysis yielded a result of 0.203. A t-value of 2.307 was considered statistically significant at the 0.025 level. With t-statistic = 6.218 and regression = 0.000, operational facilities are defined as follows: 0.454. A regression value of 0.399 and a thitung value of 4.226 define the penalty at a significance level of 0.000. The Fhitung and Sig. values were 300.417 at the same time. Among the many factors influencing workers' output, supervision stands out with the highest regression value. The workplace, its facilities, and management account for 94.3% of the variation in employee output, according to a revised R² of 0.943. The correlation between the two variables is highly significant, with an R-value of 0.973.